Application Value of Next-Generation Sequencing of Bronchial Alveolar Lavage Fluid in Emergency Patients with Infection: Application of NGS of BALF in emergency patients with infection - Wu, Weiqin; Han, Xiang; Zhao, Hongmei; Sun, Hong; Sun, Qingsong (Cellular and Molecular Biology, 2023)
This study was performed to explore the application value of next-generation sequencing (NGS) of bronchial alveolar lavage fluid (BALF) in emergency patients with infection. In this regard, a total of 52 patients with infection who were diagnosed and treated in the emergency department of our hospital from September 2019 to September 2021 were selected as the research objects. The BALF of the patients was analyzed by NGS, and the results were compared with the pathogen detection results of traditional microbial culture of the patients to analyze the diagnostic value of NGS in patients with infection. The results showed that among the 52 patients, 47 were positive by NGS and 13 were positive by traditional microbial culture. The pathogen detection rate of NGS was higher than that of traditional microbial culture[90.4% (47/52) VS 25% (13/52), χ2=45.539, P<0.001], and was able to detect viruses, fungi and other special pathogens that were difficult to be detected by traditional microbial culture, such as Chlamydia psittaci. A total of 129 pathogens were detected in the NGS test results of 47 of these patients, including bacteria, fungi, viruses and mycoplasma/chlamydia. 14 pathogens were detected in the conventional microbiological cultures of 13 patients, including bacteria and fungi. Overall, compared with traditional microbial culture methods, NGS detection has higher accuracy and can effectively detect pathogens that cannot be detected by traditional microbial culture. It has a high application value in the diagnosis of pathogens and can provide clinical guidance for the diagnosis of pathogens in patients with emergency infections.